The transformation of R&D into neo open innovation- a new concept in R&D endeavor triggered by amazon. (August 2019) - Tou, Yuji; Watanabe, Chihiro; Moriya, Kuniko; Naveed, Nasir; Vurpillat, Victor; Neittaanmäki, Pekka
Abstract: Amazon was the world's top Research and Development (R&D) firm in 2017. Its R&D investment was double that of 2015, five times that of 2012, and ten times that of 2011. Such a rapid and notable increase in R&D investment has raised the question of a new R&D definition and focus in the digital economy, which Amazon insists includes both "routine or periodic alterations" (traditionally classified as non-R&D) and "significant improvement" (classified as R&D). Using an empirical analysis of Amazon's R&D model as a system, this paper attempts to provide a convincing answer to this question. It has been identified that Amazon, which is based on R&D as a culture, has been promoting companywide experimentation to cause customers obsessed with making purchase decisions. This obsession has enabled Amazon to deploy an architecture for participation that makes the most of digital technologies by harnessing the power of users. Such user-driven innovation has accelerated a dramatic advancement of the Internet that, in turn, has accelerated the co-emergence of soft innovation resources in the marketplace. This emergence has activated a self-propagating function that has induced functionality development, leading to supra-functionality beyond an economic value that satisfies a shift in customers' preferences. While this system depends on the assimilation capacity of soft innovation resources, Amazon has developed a high level of capacity supported by a rapid and notable increase in R&D investment. The above efforts function in a virtuous cycle leading to the transformation of "routine or periodic alterations" into "significant improvement." These findings give rise to insightful suggestions regarding a new concept of R&D in neo open innovation in the digital economy. Highlights: 1 Amazon's R&D model as a system was empirically analyzed. 2 Dynamism in transforming content into technology during the R&D process was elucidated. 3 Sources leading Amazon a rapid and notable increase in R&D investment were identified. 4 Answer to a question of a new R&D definition and focus in the digital economy was provided. 5A new concept of R&D in neo open innovation in the digital economy was suggested.